Dari Kuasa Kapitalisme Tradisional Menuju Kendali Kapitalisme Digital: Studi Kasus Desainer Grafis Online Otodidak di Dusun Kaliabu - Bangsa, Petrus Gogor; Udasmoro, Wening; Noviani, Ratna (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
This study examines how self-taught online graphic designers in Kaliabu Village, Salaman District, Magelang Regency, Central Java, navigate the challenges and dependencies arising from digital platforms, particularly 99designs. Using a case study and in-depth interviews, the research reveals that, while digital technology appears to open new opportunities and empower individuals, it often reinforces control and exploitation within the digital economy. Most Kaliabu designers, lacking formal technical or creative education, leverage 99designs to access the global market, relying on self-developed skills to compete. Despite utilizing their informal capital, they are constrained by the platform's stringent rules. Although 99designs offers broad economic access, it imposes terms that limit designers' autonomy and innovation. Dependence on the platform forces designers to constantly adapt to its policies and face intense competition. The crowdsourcing system of 99designs, where projects are awarded through open competitions, exacerbates these dynamics, pushing designers to compete for every job. In the digital capitalist context, their informal capital often fails to overcome the platform's control and exploitation. This study highlights that while Kaliabu's self-taught designers can compete globally, they must navigate the balance between the freedom and control offered by digital technology. Digital technology enables participation in the digital industry but also presents challenges of control and exploitation that need addressing.